(3GdEJUGd aj YUQ GdYhdeI (B:s (3GdOhQ h GdJMOjGJ GdLOjOI (B/s - (3Sfh, ej GdYHO Gddgs ([(3Ohf ecGf(B] :s (3GdOGQ GdLGeYjI ddWHGYI h GdfTQ ,s, 1999)
(3GdGJUGd aj YUQ GdYhdeI (B, (3GdOhQ h GdJMOjGJ GdLOjOjI h ef NdGd GdOQGSI GdeJYdbI GdhSGFd GdMOjKI aj dHfGf GdJj jJVefgG gPG GdcJGH GdJYQa Gdi GKGQ GdKhQI GdJcfhdhLjI aj GdGJUGd aj dHfGf h eYQaI OhQgG aj JhKjb GdJhGUd h JWhQ GdGYdGe OGNd GdeLJeY h Hjf GdeLJeY GdeMdj h GdNGQLjs
(3HHdjhZQGajG (B: (3U(B.309-312s
Keywords: (3GdYhdeIs; (3GdEJUGds